Satellite radio wave propagation experiments in Thailand - Hemmakorn, Narong; Kitsadawanich, Surasak; Leelaruji, Nipha; Igarashi, Kiyoshi (My University, 1998)
This paper presents 2 items of satellite radio wave propagation experiments. The first experiment is to determine the variation of total ionospheric electron content (TEC) in Thailand, by using the correlation of different time delay of two L-band signals from GPS satellite. This experiment was conducted as a part of the Post-PARTNERS project of MPT, Japan. The results show that the lowest of diumal variation of TEC is just before sunrise and peak during 13:00-15:00 LT. The standard deviation of TEC data in day-time is about 15% and about 25% in night-time, the peak value occur during 2:00-5:00 LT. with 40-70% SD. The irregularity of electron density in ionosphere in night-time is greater than that in the day-time and it may cause the scintillation occured in satellite receiving signal. The second experiment is to study the down link satellite signal characteristic from Thaicom 1 and Thaicom 2 satellite. Both down link frequencies are in Kuband with different polarization. Thaicom 1 transmits in horizontal polarization while Thaicom 2 transmits in vertical polarization. The data are analyzed in two cases, the first is to analyze the amplitude scintillation characteristics. We found that the scintillation occurrence has a certain relation with the atmospheric temperature at high elevation angle and frequently occurred about 9:00 to 17:00 LT. and the maximum occurrence numbers occur during 13:00 to 15:00 LT. And the second is to analyze the receiving signal attenuation with respect to rain rate. The attenuation of signal level for one year are continuously recorded on strip charts. The result of the attenuation of receiving signal are varied due to rain rate. If the rain rate about 120 mm/hr then the received signal decrease about 4 dB/km. A comparison between the measured values and predicted value by CCIR are shown. The attenuation signal decrease about 15.4 dB, at the yearly cumulative percentage of time 0.01%. The largest value of path attenuation by rainfall is about 22 dB at the yearly cumulative percentage of time less than 0.001%.